Characterization of the 4-Hydroxybenzoyl-Coenzyme A Thioesterase from Arthrobacter sp. Strain SU - Zhuang, Zhihao (American Society for Microbiology, 2003)
The Arthrobacter sp. strain SU 4-chlorobenzoate (4-CBA) dehalogenation pathway converts 4-CBA to 4-hydroxybenzoate (4-HBA). The pathway operon contains the genes fcbA, fcbB, and fcbC (A. Schmitz, K. H. Gartemann, J. Fiedler, E. Grund, and R. Eichenlaub, Appl. Environ. Microbiol. 58:4068-4071, 1992). Genes fcbA and fcbB encode 4-CBA-coenzyme A (CoA) ligase and 4-CBA-CoA dehalogenase, respectively, whereas the function of fcbC is not known. We subcloned fcbC and expressed it in Escherichia coli, and we purified and characterized the FcbC protein. A substrate activity screen identified benzoyl-CoA thioesters as the most active substrates. Catalysis of 4-HBA-CoA hydrolysis to 4-HBA and CoA occurred with a k(cat) of 6.7 s(−1) and a K(m) of 1.2 μM. The k(cat) pH rate profile for 4-HBA-CoA hydrolysis indicated optimal activity over a pH range of 6 to 10. The amino acid sequence of the FcbC protein was compared to other sequences contained in the protein sequence data banks. A large number of sequence homologues of unknown function were identified. On the other hand, the 4-HBA-CoA thioesterases isolated from 4-CBA-degrading Pseudomonas strains did not share significant sequence identity with the FcbC protein, indicating early divergence of the thioesterase-encoding genes.